Kandungan Bakteri Escherichia Coli Pada Air Rendaman Tahu Pedagang Kaki Lima Di Pasar Kasih Naikoten 1 Kota Kupang Tahun 2017 - Agustina Agustina; Albina Bare Telan; Frengki Mboro (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2018)
One of the most common contaminants in food is Escherichia coli. These bacteria come from human and animal feces, are infected with food because of the unhygienic behavior of the handler, the washing of unclean equipment, the health of food processors and handlers and the use of washing water containing Escherichia coli. The purpose of this study was to assess the physical quality of tofu soaking raw water, assess the sanitation of tofu soaking containers and calculate the amount of E. coli soaked tofu bacteria in street vendors in the Love Market Naikoten 1 Kota Kupang in 2017. This type of research was descriptive research. with a survey approach with the size of the sample, namely 23 tofu traders in the Pasar Naik Naiken Kota Kupang. The results showed that the physical quality of tofu soaking raw water was 70% fulfilling the requirements, and 30% did not meet the requirements, soaking sanitation containers knew 66% good enough category, 17% good category and 17% poor category, E. coli bacteria content checked 4% eligible categories and 96% categories did not meet the requirements. Conclude that the physical quality of raw tofu soaking water meets the requirements, sanitation of containers used to soak the tofu well enough and the content of E. coli bacteria does not meet the requirements. The advice given is to pay attention to personal hygiene in touching food, hand hygiene and always closing the container at any time.